Beyond the diamond 21st conference : selected papers - Rugman, Alan M.; Broeck, Julien van den, 1942-; Verbeke, Alain (Emerald, 1995)
Part of a series which presents research on global strategic management, this volume focuses on the corporate response to global change. Topics discussed include strategic management and institutional dynamics, and methodological perspectives on the dynamics of national competitive advantage.
Includes indexes.
Keywords: International business enterprises -- Management.; Strategic planning.; Global economics.; elektronické knihy; electronic books